Actuarial modeling and analysis of the Hong Kong Life Annuity Scheme - KWONG, Koon Shing (Institutional Knowledge at Singapore Management University, 2019)
The Hong Kong Mortgage Corporation (HKMC) Limited, which was established in March 1997 and is wholly owned by the government of the Hong Kong Special Administrative Region, has a major mission to develop and provide different financial retirement instruments to Hong Kong residents to help address the income poverty of retirees. In June 2017, HKMC Annuity Limited, a wholly-owned subsidiary of the HKMC was incorporated to implement a new life annuity scheme which would be launched by mid-2018 to cater for the needs of cash-rich Hong Kong old age residents. The objective of the scheme is to provide an additional financial retirement planning option with minimum credit risk and a certain level of liquidity to the elderly by turning lump-sum premiums into lifetime streams of monthly income at a reasonable and stable return rate. In this paper, we establish an actuarial framework to model this life annuity scheme. The framework enables us to estimate the monthly annuity payments one might receive for a certain amount of investment. It also allows us to analyze the risk entailed in the product, thus shedding light on how the underlying risk can be managed through product design. Our findings will help potential subscribers to understand the scheme and decide whether this scheme should be included in their retirement investment portfolios when it is launched in 2018.